2009
DOI: 10.1016/j.bbi.2009.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Parental education is related to C-reactive protein among female middle aged community volunteers

Abstract: Growing evidence suggests that socioeconomic attributes of both childhood and adulthood confer risk for cardiovascular morbidity and mortality. In this study, we examine the association of both parental and individual educational attainment with C-reactive protein (CRP), an inflammatory mediator relevant to cardiovascular pathophysiology, in a midlife community sample. Subjects were 811 men and women (394 men/417 women; 87 % European-American/13 % African American), 30–54 years of age. Plasma concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 76 publications
6
36
0
Order By: Relevance
“…Three studies37–39 reported no significant associations between any measure of childhood SES and adult CRP, while further four studies23 34 40 41 reported at least one non-significant association. The remaining studies (n=14) reported significant associations between all measures of childhood SES and adult CRP 16 19 20 29 32 33 35 36 42–47…”
Section: Resultsmentioning
confidence: 97%
“…Three studies37–39 reported no significant associations between any measure of childhood SES and adult CRP, while further four studies23 34 40 41 reported at least one non-significant association. The remaining studies (n=14) reported significant associations between all measures of childhood SES and adult CRP 16 19 20 29 32 33 35 36 42–47…”
Section: Resultsmentioning
confidence: 97%
“…In the Atherosclerosis Risk in Communities Study, lower status parental occupation and education were related to higher fibrinogen levels and white blood cell count, particularly among whites (10). In other work, lower parental education was related to higher CRP levels among women but not among men (11). Brazilian men and women whose mothers had low education had elevated CRP (12).…”
Section: Introductionmentioning
confidence: 82%
“…Low childhood SES was consistently shown to be associated with chronic conditions for which both obesity and sedentary lifestyle are risk factors, such as cardiovascular disease (Wilson, D’Agostino, Sullivan, Parise, & Kannel, 2002). Moreover, socioeconomic disadvantage of the family of origin is related to elevated markers of chronic inflammation in adulthood and late life (Phillips et al, 2009). Persistent low-grade inflammation is associated positively with obesity (Harvey, Lashinger, & Hursting, 2011) and inversely with exercise (Lavie, Church, Milani, & Earnest, 2011).…”
Section: Discussionmentioning
confidence: 99%